Pengaruh Faktor Good Corporate Governance, Ukuran Perusahaan, Dan Spesialisasi Industri Auditor Terhadap Integritas Laporan Keuangan( Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2011 - 2014 ) - Kurnia Sari, Rizki; , Dr.Noer Sasongko, SE.,MSi.,Ak.,CA (2016)
This study aims to provide empirical evidence of influence: Good Corporate Governance factorsm(the Audit Committee, Independent Commissioner, Institutional Ownership, Managerial Ownership) for the integrity of financial statements, size of the company to the integrity of financial reports, and industry specialization of auditors for the integrity of the financial statements on the company's Manufacturing registered BEI in 2011-2014. This study was conducted using secondary data. The population in this study were 19 companies listed on the BEI during the period 2011-2014. The analytical method used is multiple linear regression analysis by first doing a description of the data, a classic assumption test including normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, and hypothesis testing are used is partial significance test (Uji- t), significant test simultaneous (Test F), and adjusted R Square. Results of this study prove that variabel size of the company with significant influence on the integrity of financial, while variable Audit Committee, independent directors, institutional ownership, Managerial Ownership, and industrial specialties auditor has no significant effect on the integrity of financial statements in manufacturing BEI.